2018
DOI: 10.1002/fsn3.862
|View full text |Cite
|
Sign up to set email alerts
|

Stability and in vitro digestibility of beta‐carotene in nanoemulsions fabricated with different carrier oils

Abstract: Beta‐carotene, the main dietary source of provitamin A, is required for maintaining optimum human health. The bioaccessibility of beta‐carotene can be greatly improved when ingested with fat. Therefore, the aim of the current study was to select proper oils (palm oil, coconut oil, fish oil, and corn oil) as a carrier to form stable nanoemulsion that can effectively enhance the bioaccessibility of beta‐carotene. The nanoemulsion was formulated with 90% (v/v) aqueous solution (2% whey protein isolate, WPI, w/v) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The encapsulation efficiency (EE) of EONE was determined by the ultracentrifugation method. We referred to the method of Zhou et al [31] to make appropriate modifications. Briefly, 3.0 mL of the sample was mixed with 5.0 mL of distilled n-hexane, and EO was extracted with n-hexane in a water bath at 50 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The encapsulation efficiency (EE) of EONE was determined by the ultracentrifugation method. We referred to the method of Zhou et al [31] to make appropriate modifications. Briefly, 3.0 mL of the sample was mixed with 5.0 mL of distilled n-hexane, and EO was extracted with n-hexane in a water bath at 50 °C.…”
Section: Methodsmentioning
confidence: 99%
“…However, the higher bioaccessibility measurements for the more polar lutein and zeaxanthin seen here suggest it could be a factor affecting our results. Work by Zhou et al demonstrated increased β‐carotene bioaccessibility when different carrier oils were utilized to form stable nanoemulsions, further illustrating the complexity of interactions between dietary fat and carotenoids to affect uptake (Zhou et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…2B. The lowest curcumin retention rate in LCT-based emulsions is due to the fact that LCT is an unsaturated oil (Zhou et al, 2018), which is particularly susceptible to lipid oxidation resulting in the fastest degradation of curcumin. Both SCT and MCT are saturated oils, but curcumin retention rate in SCT was higher than that in MCT.…”
Section: A 3b and 3cmentioning
confidence: 99%